The effect of two different concurrent training programs on strength and power gains in highly-trained individuals - Petre, H.; Löfving, P.; Psilander , N. (Journal of Sports Science & Medicine, 2018)
The effects of concurrent strength and endurance training have been well studied in untrained and moderately-trained individuals. However, studies examining these effects in individuals with a long history of resistance training (RT) are lacking. Additionally, few studies have examined how strength and power are affected when different types of endurance training are added to an RT protocol. The purpose of the present study was to compare the effects of concurrent training incorporating either low-volume, high-intensity interval training (HIIT, 8-24 Tabata intervals at ~150% of VO2max) or high-volume, medium-intensity continuous endurance training (CT, 40-80 min at 70% of VO2max), on the strength and power of highly-trained individuals. Sixteen highly-trained ice-hockey and rugby players were divided into two groups that underwent either CT (n = 8) or HIIT (n = 8) in parallel with RT (2-6 sets of heavy parallel squats, > 80% of 1RM) during a 6-week period (3 sessions/wk). Parallel squat performance improved after both RT + CT and RT + HIIT (12 ± 8% and 14 ± 10% respectively, p < 0.01), with no difference between the groups. However, aerobic power (VO2max) only improved after RT + HIIT (4 ± 3%, p < 0.01). We conclude that strength gains can be obtained after both RT + CT and RT + HIIT in athletes with a prior history of RT. This indicates that the volume and/or intensity of the endurance training does not influence the magnitude of strength improvements during short periods of concurrent training, at least for highly-trained individuals when the endurance training is performed after RT. However, since VO2max improved only after RT + HIIT and this is a time efficient protocol, we recommend this type of concurrent endurance training.